Crocin improves lower extremity deep venous thrombosis by regulating the PIM1/FOXO3a axis: Crocin improves lower extremity deep venous - Chen, Jun; Yang, Yi; Wang, Shuo; Zhang, Kaixin (Cellular and Molecular Biology, 2023)
Lower extremity deep venous thrombosis (LEDVT) has a high incidence and mortality. Crocin has the potential to ameliorate thrombosis. The study aimed to clarify whether crocin affects LEDVT. Human umbilical vein endothelial cells (HUVECs) were exposed to thrombin and crocin (0, 5, 10, 20, 40, and 80 μM). Cell viability was assessed by MTT assay. Cellular behaviors were assessed using flow cytometry, TUNEL assay, and tube formation assay. The binding relationship between crocin and PIM1 was analyzed by molecular docking. The underlying mechanism of PIM1 was determined by reverse transcription-quantitative PCR, dual-luciferase reporter assay, and RIP. We found that crocin (5, 10, 20, and 40 μM) promoted thrombin-treated HUVEC viability in a dose-dependent manner. Crocin inhibited apoptosis and promoted the angiogenesis of HUVECs induced by thrombin. PIM1 was a target of crocin and was upregulated in patients with LEDVT and thrombin-treated cells. Foxo3a could interact with PIM1 and positively related to PIM1 expression. Moreover, the knockdown of PIM1 suppressed apoptosis and promoted angiogenesis in thrombin-HUVECs treated with crocin, while overexpression of Foxo3a reversed the effects. In conclusion, crocin inhibited apoptosis and promoted the angiogenesis of HUVECs induced by thrombin via the PIM1/Foxo3a axis, suggesting that crocin may be effective for LEDVT therapy.